Convergence in agriculture of some Asian countries - Erniel B. Barrios (Asian Development Bank Institute (ADBI), 2007)
An agricultural growth model is proposed to verify the agricultural convergence hypothesis among some Asian countries following the method of Barro and Sala-i-Martin (1992) and Sala-i-Martin (1996). Conditional convergence of agriculture is facilitated by foreign aid intended for agriculture and spatial externalities associated with foreign trade. However, foreign aid for agriculture may not serve the purpose of mobilizing resources for an environment conducive to development, but rather may function as a substitute to public expenditure for the sector.
Keywords: Q17; O13; H50; 330; agricultural growth; convergence; trade; foreign aid; public expenditures; Entwicklungskonvergenz; Landwirtschaftliche Entwicklung; Außenwirtschaft; Entwicklungshilfe; Öffentliche Ausgaben; Asien